Triblock Terpolymers by Simultaneous Tandem Block Polymerization (STBP). Issue 3 (7th December 2015) - Freudensprung, Ines; Klapper, Markus; Müllen, Klaus
Abstract : A route of synthesizing triblock terpolymers in a one‐pot, "one‐step" polymerization approach is presented. The combination of two distinct polymerization techniques through orthogonal catalyst/initiator functionalities attached to a polymeric linker furnishes novel pathways to ABC‐terpolymers. Both polymerizations have to be compatible regarding mechanisms, chosen monomers, and solvents. Here, an α, ω‐heterobifunctional poly(ethylene glycol) serves as polymeric catalyst/initiator to obtain triblock terpolymers of poly(norbornene)‐ b ‐poly(ethylene glycol)‐ b ‐poly(l ‐lactic acid) PNB‐PEG‐PLLA via simultaneous ring opening metathesis polymerization and ring opening polymerization in a fast one‐pot polymerization. Structural characterization of the polymers is provided via 1 H‐, DOSY‐, and 1 H, 1 H‐COSY‐NMR, while solution and thin film self‐assembly are investigated by dynamic light scattering and atomic force microscopy. Abstract : A widely applicable one‐pot synthetic procedure is demonstrated here for the synthesis of triblock terpolymers. The simultaneous tandem block polymerization is carried out by a combination of ring opening metathesis polymerization and ring opening polymerization on a heterobifunctional PEG‐macroinitiator which leads within 15 min to triblock terpolymers. Monomers with different polarities can be combined, obtaining polymers undergoing strong phase separation, whose solution and thin film self‐assembly are studied.